Data collection from images: considerations on the users' privacy in social networks - Assumpcao, Fabricio Silva [UNESP]; Goncalves Santana, Ricardo Cesar [UNESP]; Costa Santos, Placida Leopoldina V. A. da [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2015)
Considering the privacy concerns on users' data in social networks, the role of images on social networks and the images as data sources, this paper aims to identify how data collection from images is treated in Facebook and Instagram. For this, we identify the main methods for data collection from images, the mentions to data collection from images in Facebook and Instagram policies, and the options that are presented to users for setting up the data collection from images. We conclude that the policies analyzed are vague in several points regarding to data collection from images: they do not specify which data are collected and just list items with an illustrative purpose. These findings highlight the need for studies and actions to raise awareness of social networks users about their privacy in data collection.
Keywords: Privacy; Data collection; Image; Facebook; Instagram